Efeito agudo do treinamento intervalado de alta intensidade (hiit) no balanço redox de ratas submetidas à dieta hiperlipídica - Martins, Jonathan Elias Rodrigues (2021)
The aim of this study were (1) to analyze the effects of high-intensity interval training (HIIT) in Wistar rats submitted to a high-fat diet on redox homeostasis, and (2) to identify the potential molecular markers in skeletal muscle tissue for future biotechnological applications. Thirty-six Wistar rats were used, which were divided into two groups according to the ad libitum diet for 56 days: Standard Diet group (SD, n=20) (380.0 kcal/100 g; Lipids = 4.0 g/100 g) and Hyperlipidic Diet group (HFD, n=20) (406.9 kcal/100 g; Lipids = 14.2 g/100 g). Subsequently, the groups were subdivided into Sedentary SD (SD, n=10), Exercise SD (SD-Ex, n=10), Sedentary HFD (HFD, n=10) and Exercise HFD (HFD-Ex, n=10). The animals were adapted to the treadmill for two weeks at low speed, five days a week. After adaptation, a maximum incremental test (MIT) determined the maximum capacity of the animals. Then, a supraaerobic acute HIIT session was performed, which consisted of 5 sets of 5 minutes with passive rest of 5 minutes. The animals were euthanized and the perigonadal, subcutaneous and visceral fats, as well as the gastrocnemius muscle were dissected for subsequent biochemical analyzes of the bioenergetics parameters (lactate), cellular damage (GSH) and antioxidant enzymes activities (SOD, CAT and GPX). In addition, the transcriptional profile of the redox balance markers (Slc2a4, Cs, Pparg1-α, Fndc5, Nox4, Sod1, Sod2, Cat, and Gpx1) was also determined. Statistical analysis was performed using unpaired Student's t test and Mann-Whitney test for comparison of groups, as well as two-way ANOVA and Bonferroni's post-hoc test. The data were expressed as mean±standard error of the mean with significance probability of P<0.05. As results, no significant differences were observed among groups regarding the phases of estrous cycle. The total fat mass in the HFD and HFD-Ex groups was significantly higher than SD and SD-Ex groups. As for the bioenergetics markers, a significant increase was observed in the expression of Cs and Pparg1-α in the white fibers of the SD-Ex group compared to the other groups; whereas for red fibers, the increase was observed in the HFD-Ex group. Slc2a4 expression was significantly higher in the white fibers of the SD-Ex group compared to the other groups; while in the red fibers, this increase was observed in both groups submitted to exercise (SD-Ex and HFD-Ex). Regarding Fndc5, its expression was significantly higher in the white fibers of both groups submitted to physical exercise (SD-Ex and HFD-Ex); whereas, in the red fibers, only the SD-Ex group presented increased results when compared to the other treatments. The relative expression of Cat in white fibers was significantly higher in SD-Ex group when compared to SD and HFD. On the other hand, the relative expression of GSH wasnot different among groups in both white and red fibers. Based on these results, it can be concluded that excess adiposity can impair antioxidant defense according to the type of fiber and that HIIT could alleviate its deleterious effects on skeletal muscle.